2006
DOI: 10.1007/s10620-006-9241-y
|View full text |Cite
|
Sign up to set email alerts
|

Uninvestigated Dyspepsia in Latin America: A Population-Based Study

Abstract: We sought to assess the prevalence, severity of symptoms, and risk factors of uninvestigated dyspepsia in a population-based study in Argentina. Eight hundred thirty-nine valid questionnaires were evaluated. Dyspepsia was present in 367 subjects (43.2%; 95% confidence interval [CI], 39.8-46.6); 110 (13.6%) had overlap with gastroesophageal reflux disease (GERD). The group with dyspepsia without GERD consisted of 257 subjects (29.6%; 95% CI, 26.5-32.7), 183 (71.1%) had ulcer-like dyspepsia, and 74 (28.9%) had d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
0
6
0
2
Order By: Relevance
“…31 Haque et al 32 also examined the prevalence of dyspepsia and reflux symptoms in 1,000 adults in New Zealand, and found that 63% of subjects with reflux symptoms had symptoms of dyspepsia, while 56% of subjects with dyspepsia also had reflux symptoms. Similarly, overlap of GERD with uninvestigated dyspepsia was 13.3% in Argentina 33 and 33.8% in Belgium, 34 and overlap of GERD was 30-40% in patients with FD (Rome III) in Japan, 35 and 48.8% in subjects with FD (Rome III) in US. 36 Although there were differences in the prevalence of heartburn or GERD in dyspepsia/FD in each country, overlap of GERD and dyspepsia/FD is clearly a common observation.…”
Section: Dyspepsia With Upper Gastrointestinal Diseases (Heartburn Ormentioning
confidence: 87%
“…31 Haque et al 32 also examined the prevalence of dyspepsia and reflux symptoms in 1,000 adults in New Zealand, and found that 63% of subjects with reflux symptoms had symptoms of dyspepsia, while 56% of subjects with dyspepsia also had reflux symptoms. Similarly, overlap of GERD with uninvestigated dyspepsia was 13.3% in Argentina 33 and 33.8% in Belgium, 34 and overlap of GERD was 30-40% in patients with FD (Rome III) in Japan, 35 and 48.8% in subjects with FD (Rome III) in US. 36 Although there were differences in the prevalence of heartburn or GERD in dyspepsia/FD in each country, overlap of GERD and dyspepsia/FD is clearly a common observation.…”
Section: Dyspepsia With Upper Gastrointestinal Diseases (Heartburn Ormentioning
confidence: 87%
“…Recently, there was a population-based study in Argentina to assess the prevalence, severity of symptoms and risk factors for uninvestigated dyspepsia [26]. They showed that the annual prevalence of dyspepsia in Argentina was 43.2% and the prevalence of dyspepsia without GERD was 29.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Its prevalence in the general population varies according to studies, probably in relation with the definition [3]. As a result, it is 29% in Canada [4], 44.1% in the US [5], 38% in the United Kindom [6], 25% in France [7].…”
Section: Introductionmentioning
confidence: 99%